Characterization of oxygen functional groups on carbon surfaces with water and methanol adsorption. (January 2015) - Zeng, Yonghong; Prasetyo, Luisa; Nguyen, Van T.; Horikawa, Toshihide; Do, D.D.; Nicholson, D.
Abstract: We propose a new method, using the ambient temperature adsorption of methanol in the Henry law region as a molecular probe, to determine the concentration of surface oxygen functional groups ( Cα ) on carbon adsorbents. Two adsorbents: porous A5 and non-porous Carbopack F have been chosen here as experimental examples. The theoretical Henry constant ( Kα ) is the product of the intrinsic interaction between a methanol molecule and one functional group, α, having a concentration ( Cα ) and is estimated by carrying out a volume integration of the Boltzmann factor for methanol interacting with the functional group. Our results show that Cα determined with methanol for A5 compares well with that determined previously with water as the molecular probe (Nguyen, 2014 [1]); and both are in good agreement with results from Boehm titration. For Carbopack F, we find that Cα, determined by methanol adsorption, gives more realistic concentrations than those obtained by Boehm titration, which are subject to large errors because of the very low concentration of the functional groups. The method proposed here is fast and easy to implement, and serves as an alternative to the Boehm titration technique.